Regulation of basal body and ciliary functions by Diversin - Yasunaga, Takayuki (2011)
The centrosome is essential for the formation of the cilia and has been implicated in cell polarization and signaling during early embryonic development. A number of Wnt pathway components were found to localize at the centrosome, but how this localization relates to their signaling functions is unclear. In this study, we assessed a role for Diversin, a putative Wnt pathway mediator, in developmental processes that involve cilia. We find that Diversin is specifically localized to the basal body compartment near the base of the cilium in Xenopus multi-ciliated skin cells. Overexpression of Diversin RNA disrupted basal body polarization in these cells, suggesting that tightly regulated control of Diversin levels is crucial for this process. In cells depleted of endogenous Diversin, basal body structure appeared abnormal and this was accompanied by disrupted polarity, shortened or absent cilia and defective ciliary flow. These results are consistent with the involvement of Diversin in processes that are related to the acquisition of cell polarity and require ciliary functions.